ESG News, Future Cash Flows, and Firm Value - DERRIEN, FRANÇOIS; KRÜGER, PHILIPP; LANDIER, AUGUSTIN; YAO, TIANHAO (Journal of Finance, 2025)
ABSTRACT We investigate the expected consequences of negative environmental, social, and governance (ESG) news on firms' future profits. After learning about negative ESG news, analysts significantly downgrade their forecasts at short and longer horizons. Negative ESG news affects forecasts more strongly at longer horizons than other types of negative corporate news. The negative revisions of earnings forecasts following negative ESG news largely reflect expectations of lower future sales, rather than higher future costs. Quantitatively, forecast revisions can explain most of the negative impacts of ESG news on firm value. Analysts are correct to revise forecasts downward following negative ESG news.